Estimates of cost functions and costs of various post harvest handling activities of paddy in Malaysia - Mohayidin, Mohd. Ghazali (1986)
In this paper, cost estimates of individual components of post-harvest operations of paddy have been obtained from the data collected during the 1984-85 harvesting season. Models of assembly, milling and drying costs have been developed. In addition, individual cost components of the marketing chain have been generated. The reseults indicate significant differences across cost categories and these differences account for the different harvesting operations especially when compared with those of other ASEAN countries.